Influenza A viruses circulating in dogs - a review of the scientific literature - Nailya Klivleyeva; Tatyana Glebova; Mira Shamenova; Nurbol Saktaganov (Open Veterinary Journal, 2022)
Influenza A viruses (IAV) cause persistent epidemics and occasional human pandemics, leading to considerable economic losses. The ecology and epidemiology of IAV are very complex and the emergence of novel zoonotic pathogens is one of the greatest challenges in the healthcare. IAV are characterized by genetic and antigenic variability resulting from a combination of high mutation rates and a segmented genome that provides the ability to rapidly change and adapt to new hosts. In this context, available scientific evidence is of great importance for understanding the epidemiology and evolution of influenza viruses. The present review summarizes original research papers and IAV infections reported in dogs all over the world. Reports of interspecies transmission of equine influenza viruses (EIV) H3N2 from birds to dogs, as well as double and triple reassortant strains resulting from reassortment of avian, human and canine strains have amplified the genetic variety of canine influenza viruses. A total of 146 articles were deemed acceptable by PubMed and the Google Scholar database and were therefore included in this review. The largest number of research articles (n=68) were published in Asia, followed by the Americas (n=44), Europe (n=31), Africa (n=2) and Australia (n=1). Publications are conventionally divided into three categories. The first category (largest group) included modern articles published from 2011 to the present (n=93). The second group consisted of publications from 2000 to 2010 (n=46). Single papers of 1919, 1931, 1963, 1972, 1975, and 1992 were also used, which was necessary to emphasize the history of the study of the ecology and evolution of the IAV circulating among various mammalian species. The largest number of publications occurred in 2010 (n=18) and 2015 (n=11), which is associated with IAV outbreaks observed at that time in the dog population in America, Europe and Asia. In general, these findings raise concerns that dogs, may mediate the adaptation of IAVs to zoonotic transmission and therefore serve as alternative hosts for genetic reassortment of these viruses. The global concern and significant threat to public health from the present COVID-19 pandemic confirms the necessity for active surveillance of zoonotic viral diseases with pandemic potential. [Open Vet J 2022; 12(5.000): 676-687]